Women's Position in Lithuanian Labour Market in the 20th century - Virginija Jureniene (Amnis)
The paper draws attention to women's position in the changing labour market of the 1920s-1930s and after the reestablishment of independence in 1990 in the Republic of Lithuania. The author carries out a historical analysis of the impact of the laws issued at that period to solve the issue of unemployment and explores their implications to women's position in the labour market. Among the most significant laws dealing with rising unemployment in Lithuania at the beginning of the 20th century was the one demanding from an employer to dismiss an employee whose spouse had a job. Since the society of that time was predominantly patriarchal, married women were the first to be dismissed. The law raised a stormy reaction from women who sought support from international organizations such as the Federation of International Diplomaed Women and the Union of the Nations. However, the issue was not solved till 1940 and burst out after the reestablishment of the state in 1990 and persisted till 1998 when the law of Equal Opportunities was issued.